Pengaruh Kombinasi Pijat Marmet dan Pijat Oksitosin terhadap Produksi Asi pada Ibu Nifas di Wilayah Kerja Puskesmas Oesao Kabupaten Kupang - Ni Putu Indu Dewi Pradnyani Murti; Atalia Pili Mangngi; Bernadeta Erni; Deviserlina Babys; Fitria Atapukang; Windy Anisa Veryany Fanggi (Lembaga Pengembangan Kinerja Dosen, 2025)
Mother's milk (ASI) has an important role in increasing the baby's immune system and baby's weight. Breast milk production that is not strong enough causes the baby's needs to not be fulfilled and the failure of exclusive breastfeeding. Based on a survey conducted by the research and development agency in the field of Health, it was found that 46% of the inability to breastfeed occurred due to lack of breast care, 25% due to the frequency of breastfeeding less than 8x/day, 14% due to newborns (LBW), 10% premature, and 5% due to acute or chronic disease. The decrease in breast milk production during the puerperium can be caused by a lack of stimulation of the hormones prolactin and oxytocin which play a very important role in the smooth production of breast milk. Marmet massage and oxytocin massage are safe ways to stimulate the breasts to produce more milk.